PERAN PETUGAS KESEHATAN DALAM MANAJEMEN PENANGANAN BENCANA ALAM - JULIANTI SITOMPUL (LP2MTBM MAKARIOZ, 2018)
The writing of this paper aims to determine the role of health workers in the management of handling natural disasters. Writing methods using the library research method From the discussion it can be concluded that one successful condition for handling disaster emergencies is leadership. The absence or weakness of leadership is confusion, destruction of loss, and disaster. The leadership meant is of course the element of authority (government). The success of all elements of society in the disaster scene depends on the presence of the leader. Leadership in handling disaster emergencies must be able to be quick, precise, and dare to make decisions, be assertive, run an instruction system instead of discussion